Diagnosis of Phlebotomas Argentipes as a Vector for Visceral Leismaniasis by PCR in Bangladesh (Update Dental College Journal, 2018)
Objectives: The present study was undertaken to diagnose sandfly as a vector of visceral leismaniasis by PCR in Bangladesh.  Place and period of study: The study was conducted in Fulbaria Upazilla of Mymensing District during 2001-2004.Materials & Methods: The study was conducted in the department of Microbiology, National Institude of Preventive and social medicine (NIPSOM), Mohakhali, Dhaka. DNA extraction from Sand Fly: All the procedure followed for DNA extraction from Bone marrow is same for sandfly except AL buffer where instead of AL buffer ATL buffer were added. The primers used are constructed from kDNA of L.  (L) donovani. DD8 strain to amplify a fragment of 354 bp in length.Results: PCR of extracted DNA from sandfly (P.argentipes) revealed 354 bp bands similar to buffy coat and bone mamow samples containing DNA of L. Donovani. This might be the first demonstration of L.donovani parasite in sand fly vector in Bangladesh.Conclusion: The present study shows that PCR is a good diagnostic tool for the demonstration of L.donovani parasite for the P.argentips sp in Bangladesh.Update Dent. Coll. j: 2017; 7 (2): 15-18